Evaluación de parámetros ecológicos de la regeneración natural en los claros, del bosque tropical de montaña, en la estación científica San Francisco - Jiménez Largo, Leonardo Agustín (2015)
This research was focused on the floristic characterization and evaluation of ecological parameters of natural regeneration in the glades of the tropical mountain forest; into permanent plots established in the watershed Q5, located in the San Francisco Scientific Station; in which a silvicultural treatment was applied in 2004. In the field phase, data of height, diameter at the height of the base (DHB) and plant health of each individual were registrated; also opening of the canopy of each plot was measured. In the desk phase, the floristic composition of natural regeneration in glades was determined; ecological parameters of natural regeneration as: height, basal diameter, abundance, density, frequency, wealth, alpha diversity, mortality rate, recruitment rate, annual periodic growth, and finally the opening of the canopy in the establishment and development of the natural regeneration in glades were evaluated. The results were compared with data obtained in two previous evaluation. The formation of the glades by the application of silviculture treatment and the own dynamic existing in the forest, influenced in the floristic composition and in the establishment of the number of families, kind, species and individuals; as well as ecological parameters of natural regeneration, since significant variations were evidenced in the plots established in the different assessment periods. The most representative families in terms of species were: Solanaceae, Lauraceae, Piperaceae, Mimosaceae, Rubiaceae, Arecaceae, Euphorbiaceae, Melastomataceae and Meliaceae